An investigation on the influence of nano silica morphology on the characteristics of cement composites. (July 2020) - Kooshafar, Mohammad; Madani, Hesam
Abstract: Nanosilica is produced with various methods and each product has particular applications in the industry. The differences between the nanosilicas are mainly attributed to their morphology. For instance, some types of nanosilicas such as nanosilica gels have large agglomerates, while some others like nanosilica sols may be produced in the monodispersed form. The main objective of this article is investigating the differences between the influences of agglomeration state of nanosilica, as an aspect of morphology, on the characteristics of cement composites. Among the nanosilica types, nanosilica gel has been scarcely investigated in the cement based materials researches. Thus, a simple method for production of nanosilica gel is presented. Then, the characteristics of cement mixtures containing this material have been compared with those incorporating a monodispersed nanosilica sol and silica fume. The properties investigated in this study include shrinkage measurements, compressive strength, water sorptivity, cement hydration, flow ability, setting times and rapid chloride migration coefficient. The results indicate that, despite the agglomeration state, at early ages, nanosilica gel outperformed the silica sol and silica fume in improving the characteristics such as compressive strength. It confirms that the monodispersed form of nanosilica sol could not provide higher levels of nucleation centers in the mixture; in other words, coagulation of nano particles is inevitable in the environment of cement-based materials. Likewise, at long term, nanosilica gel incorporated concretes had improved durability in terms of chloride penetration and water sorptivity compared to those with monodispersed nanosilica sol. Highlights: The morphology of Nano silica materials and their agglomeration state could influence the properties of cement composites. Nanosilicas improved the compressive strength, accelerating effect on cement hydration and setting times of cement mixtures. The durability test results reveal that replacing cement with nanosilicas led to improved microstructure. By incorporating nanosilicas in the cement mixtures, the workability was significantly reduced. The mixtures containing nano silicas had higher shrinkage values compared to the plain mixture.